Antioxidant Activities, Physicochemical and Sensory Quality Attributes of Steam Milk Dodol Using Red Rice Flour - Hatta, Wahniyathi; Ningrum, Endah Murphi; Yuliati, Farida Nur; Syawal, Sutomo (Faculty of Animal Science, Universitas Brawijaya, 2025)
Red rice exhibits high antioxidant activities due to its significant levels of anthocyanins. Incorporating red rice into milk dodol production is expected to enhance product functionality. This research examined the effect of substituting glutinous rice flour with red rice flour at varying proportions on the quality of steamed milk dodol. The study employed a completely randomized design with a single factor (proportions of red rice flour to glutinous rice flour: 30:70, 40:60, and 50:50). Each treatment was replicated three times. Quality parameters included anthocyanin content, antioxidant activity, TBA value, proximate composition, reducing sugar content, color values (L*, a*, b*), water activity, and sensory quality. Increasing the proportion of red rice flour significantly increased (p<0.01) anthocyanin levels, antioxidant activity, reducing sugar content, and redness (a*), but significantly decreased (p<0.01) water content, fat content, and yellowness (b*). No significant differences (P<0.05) were observed in TBA value, protein content, ash content, brightness (L*), water activity, and sensory quality with increasing red rice flour proportion. Thus, substituting up to 40% glutinous rice flour with red rice flour improved the quality and functionality of steamed milk dodol without compromising acceptability.